Finance and Technology: Challenges and Solutions - Milind Sathye (International Conferences SDGs 2030 Challenges and Solutions, 2030)
The theme of the conference is the challenges to achieving the sustainabledevelopment goals and the possible solutions thereto. The Asian DevelopmentBank1 lists the 17 sustainable development goals and progress there under intheir report titled the Asia Pacific Sustainable Development Goals Outlook releasedrecently. The last of these goals, SDG 17 refers to finance, technology and trade.I will focus on the challenges in achieving this goal and possible solutions theretobased on my experience as a development banker for nearly two decades. Beforebecoming a banking and finance academic in Australia, I worked for nearly 20years in the Reserve Bank of India and its outfit the National Bank for Agricultureand Rural Development (NABARD). As an academic, the focus of my research ismicro finance and the use of financial technology. I will draw up on the studiesconducted by me.